2013
DOI: 10.1159/000355161
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Eosinophilic Esophagitis by Sublingual Pollen Immunotherapy

Abstract: Sublingual immunotherapy (SLIT) is increasingly investigated and utilized for the treatment of food and pollen allergies. Previous case reports suggested that eosinophilic esophagitis (EoE) might develop as a long-term complication in children after completion of oral immunotherapy. Here, we describe a 44-year-old female with a medical history of pollinosis who for the first time in her life developed complete manifestation of EoE (peak eosinophils 164/high power field) 4 weeks after initiation of SLIT using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(62 citation statements)
references
References 13 publications
3
55
0
4
Order By: Relevance
“…This was illustrated by one subject that developed acute eosinophilic esophagitis after exposure to sublingual immunotherapy that included typical airborne antigens such as hazelnut, birch and alder. This esophageal response resolved clinically and endoscopically after the immunotherapy was discontinued [48] . There is also experimental evidence in wild mice that repeated nasal inoculation with allergens such Aspergillus fumigatus triggers an eosinophilic infiltration of the esophagus.…”
Section: Pathogenesismentioning
confidence: 92%
“…This was illustrated by one subject that developed acute eosinophilic esophagitis after exposure to sublingual immunotherapy that included typical airborne antigens such as hazelnut, birch and alder. This esophageal response resolved clinically and endoscopically after the immunotherapy was discontinued [48] . There is also experimental evidence in wild mice that repeated nasal inoculation with allergens such Aspergillus fumigatus triggers an eosinophilic infiltration of the esophagus.…”
Section: Pathogenesismentioning
confidence: 92%
“…Since then, it has been progressively applied as a treatment for food and pollen allergies in adults and children [97] . EoE has been repeatedly reported as an adverse reaction following OIT with milk, egg, and peanut, but it has also been reported to happen following SLIT in some cases.…”
Section: Slit and Eoementioning
confidence: 99%
“…For the first time, Miehlke et al [97] presented a 44-year-old woman, who demonstrated the clinical symptoms of EoE following SLIT. She was receiving SLIT with a combination of hazelnut, birch, and alder extracts for the treatment of her allergic rhinitis and asthma and Bauer et al [98] also reported a 9-year-old autistic boy with a history of allergic rhinoconjunctivitis, asthma, and severe feeding disturbance.…”
Section: Slit and Eoementioning
confidence: 99%
See 1 more Smart Citation
“…With increasing awareness for EoE in the future, it is likely that dysphagia itself will become the most prominent symptom leading to a rapid diagnosis of EoE in adults. Dysphagia may also be a quite early event in the development of EoE as suggested by a case of a 44-year-old woman who rapidly developed a full clinical picture of de novo EoE including severe dysphagia, confluent white exudates on endoscopy and severe eosinophilic inflammation of esophageal biopsies within the first 4 weeks of sublingual immunotherapy for hay fever [11]. …”
Section: Symptom Presentation Of Eoementioning
confidence: 99%